Preferensi dan pola konsumsi sayur dan buah pada remaja - Badriyah, Lulu’ul; Paramita, Farah; Lenggono, Kumoro Asto; Veronica, Shanica Yohana; Indrayati, Alifia Meida; Gustawan, Randy (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Fruit and vegetable consumption is an important factor in a balanced nutritional pattern that supports adolescent health. However, consumption and preference for fruit and vegetables in Indonesia, especially among adolescents, are still low and do not meet the WHO recommendation of 400 grams per day. This study was conducted to determine fruit and vegetable preferences and consumption patterns among adolescents in East Java. Purpose: To determine fruit and vegetable preferences and consumption patterns among adolescents. Methods: This study used a cross-sectional study design with a sample of 132 high school students in four regencies/cities in East Java, selected using purposive sampling. The instruments used were questionnaires and food frequency questionnaires (FFQs). Data were analyzed descriptively using univariate analysis. Results: Adolescents preferred spinach the most (mean = 3.50 ± 0.59) and bitter melon the least (mean = 1.67 ± 0.78). The top favorite vegetables were spinach, carrots, broccoli, kale, and cucumber, with regional variations: carrots in Batu City and Malang Regency, and spinach in Pasuruan Regency and Malang City. Among fruits, mango ranked highest (mean = 3.82 ± 0.52) and passion fruit lowest (mean = 2.91 ± 0.89). Mango was the favorite fruit in three regions, followed by apples in Pasuruan Regency, while langsat and passion fruit were consistently less popular across all regions. Conclusion: The most popular vegetable among adolescents was spinach, while the least popular was bitter melon. The most popular fruit among adolescents was mango, while the least popular was passion fruit. Education regarding vegetables and fruits, as well as innovations in various processed products, are needed to increase preferences and diversity in fruit and vegetable consumption. Keywords: Adolescents; Consumption Patterns; Fruit; Preferences; Vegetables. Pendahuluan: Konsumsi sayur dan buah merupakan faktor penting dalam pola gizi seimbang yang mendukung kesehatan remaja. Namun, konsumsi dan preferensi terhadap sayur dan buah di Indonesia, khususnya di kalangan remaja, masih rendah dan belum memenuhi rekomendasi WHO sebesar 400 gram per hari. Penelitian ini dilakukan untuk mengetahui preferensi dan pola konsumsi sayur dan buah pada remaja di Jawa Timur. Tujuan: Untuk mengetahui preferensi dan pola konsumsi sayur dan buah pada remaja. Metode: Penelitian ini menggunakan desain studi cross-sectional dengan sampel 132 siswa SMA di 4 Kabupaten/Kota Jawa Timur yang diambil secara pusposive sampling. Instrumen yang digunakan adalah kuesioner dan formulir food frequency questionnaire (FFQ). Data dianalisis secara deskripti menggunakan analisis univariat. Hasil: Remaja paling menyukai bayam (mean = 3.50 ± 0.59) dan paling tidak menyukai pare (mean = 1.67 ± 0.78). Sayuran favorit utama adalah bayam, wortel, brokoli, kangkung, dan timun, dengan variasi wilayah: wortel di Kota Batu dan Kabupaten Malang, serta bayam di Kabupaten Pasuruan dan Kota Malang. Pada buah, mangga menempati peringkat tertinggi (mean=3.82 ± 0.52) dan markisa terendah (mean=2.91 ± 0.89). Mangga menjadi buah favorit di tiga wilayah, sedangkan apel di Kabupaten Pasuruan, sementara duku dan markisa konsisten kurang disukai di seluruh wilayah. Simpulan: Sayuran yang paling disukai remaja adalah bayam dan tidak disukai adalah pare. Buah-buahan yang paling disukai remaja adalah mangga dan tidak disukai adalah markisa. Diperlukan edukasi terkait sayur dan buah serta inovasi berbagai olahan sayur dan buah untuk meningkatkan preferensi dan keberagaman konsumsi sayur dan buah. Kata Kunci: Buah; Pola Konsumsi; Preferensi; Remaja; Sayur.